Pendampingan Membaca Tulis Al-Quran Bagi Anak Madrasah Itidaiyah di Desa Jaring Halus Kabupaten Langkat - Asparudin; Desy Putri Rivayanty; Mitha Dwi Andrianti; Anjur Perkasa Alam (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
Qur'anic education is essential in shaping the character of a qualified Islamic generation. This activity is carried out in response to the challenges of the times, where the younger generation is increasingly affected by globalisation and negative associations. This paper discusses community service that aims to increase children's interest and understanding of the Qur'an through learning assistance. Activity methods include lectures, question and answer, practice, sociodrama, and storytelling. The implementation process is divided into introduction, implementation, and evaluation stages. The results show a significant increase in the ability to read and memorise the Qur'an in children. Assistance is carried out by starting from a pre-test to measure the initial ability of children, then dividing groups based on the results of the pre-test. The children were guided in reciting the Quran, depositing their memorisation, and starting new memorisation. Islamic material is delivered in theory and practice, such as the procedure for washing. Afterwards, a post-test was conducted to evaluate the children's progress. This activity succeeded in improving the recitation of the Qur'an, increasing self-confidence, and strengthening religious values in children. The positive response from the school and the management showed the success of this service.